Phase behaviour of the ternary system: monoolein-water-branched polyethylenimine - Kumar, Manoj; Kumaraswamy, Guruswamy (Soft Matter, 2015)
Addition of a branched polymer, polyethyleneimine, significantly alters the organization of a glycerol monooleate (GMO) lipid-water system. We present detailed data over a wide range of compositions (water content from 10 to 40%, relative to GMO and PEI fractions from 0 to 4%) and temperatures (25-80 degrees C). The PEI molecular weight effects are examined using polymers over a range from 0.8 to 25 kDa. Addition of PEI induces the formation of higher curvature reverse phases. In particular, PEI induces the formation of the Fd3m phase: a discontinuous phase comprising reverse micelles of two different sizes stacked in a cubic AB(2) crystal. The formation of the Fd3m phase at room temperature, upon addition of polar, water soluble PEI is unusual, since such phases typically are formed only upon addition of apolar oils. The largest stability window for the Fd3m phase is observed for PEI with a molecular weight = 2 kDa. We discuss how PEI influences the formation and stability of high curvature phases.